Dr Jekyll and Mr Hyde - Dowswell; Paul (London Usborne Publishing Ltd, 2021)
Dr. Henry Jekyll is well-liked and admired by his friends, but seems increasingly troubled and withdrawn from their company. Meanwhile, a mysterious and repellent character, Mr. Hyde, commits crime after crime. What hold can he have over the admirable Dr. Jekyll?